Essential Enterprise Blockchain Concepts and Applications - Saini, Kavita; Chelliah, Pethuru Raj.; Saini, Deepak Kumar (Milton : Auerbach Publishers, Incorporated, 2021)
Blockchain is a technology that has attracted the attention of all types of businesses. Cryptocurrency such as Bitcoin has gained the most attention, but now companies are applying Blockchain technology to develop solutions improving traditional applications and securing all types of transactions. Robust and innovative, this technology is being combined with other well-known technologies including Cloud Computing, Big Data, and IoT to revolutionize outcomes in all verticals. Unlike books focused on financial applications, Essential Enterprise Blockchain Concepts and Applications is for researchers and practitioners who are looking for secure, viable, low-cost, and workable applications to solve a broad range of business problems. The book presents research that rethinks how to incorporate Blockchain with existing technology. Chapters cover various applications based on Blockchain technology including: Digital voting Smart contracts Supply chain management Internet security Logistics management Identity management Securing medical devices Asset management Blockchain plays a significant role in providing security for data operations. It defines how trusted transactions can be carried out and addresses Internet vulnerability problems. Blockchain solves the security fault line between AI and IoT in smart systems as well as in other systems using devices connected to each other through public networks. Linear and permanent indexed records are maintained by Blockchain to face the vulnerability issues in a wide variety applications. In addition to applications, the book also covers consensus algorithms and protocols and performance of Blockchain algorithms.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); COMPUTERS / Cryptography; MATHEMATICS / General; COMPUTERS / Enterprise Applications